Hydrogenation of Zr-2.5Nb alloy after plasma-immersion titanium implantation - Sutygina A. N. Alina Nikolaevna; Kashkarov E. B. Egor Borisovich; Nikitenkov N. N. Nikolai Nikolaevich; Tyurin Yu. I. Yuri Ivanovich; Syrtanov M. S. Maksim Sergeevich (2016, 2016)
Title screen